2018
DOI: 10.5152/eurjrheum.2018.18162
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of secukinumab and adalimumab in ankylosing spondylitis as assessed by matching-adjusted indirect comparison

Abstract: ObjectiveMatching-adjusted indirect comparison was used to assess the comparative effectiveness of secukinumab 150 mg and adalimumab 40 mg in biologic-naïve patients with ankylosing spondylitis (AS) for up to 1 year.MethodsPooled individual patient data from the secukinumab arms of MEASURE 1 (NCT01358175) and MEASURE 2 (NCT01649375) trials (n=197) were matched against the ATLAS (NCT00085644) adalimumab population (n=208). Logistic regression analysis was used to determined weights to match for age, sex, Bath A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Thus, in this study, we analyzed only the data from biologic‐naïve patients to identify the efficacy of secukinumab as the primary biologic agent and found that efficacy of secukinumab was consistently comparable with adalimumab. This finding is consistent with the results of a recently published matching‐adjusted indirect comparison study that showed no significant differences in ASAS 20 and 40 response rates between secukinumab and adalimumab …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, in this study, we analyzed only the data from biologic‐naïve patients to identify the efficacy of secukinumab as the primary biologic agent and found that efficacy of secukinumab was consistently comparable with adalimumab. This finding is consistent with the results of a recently published matching‐adjusted indirect comparison study that showed no significant differences in ASAS 20 and 40 response rates between secukinumab and adalimumab …”
Section: Discussionsupporting
confidence: 92%
“…25 Thus, in this study, we analyzed only the data from comparison study that showed no significant differences in ASAS 20 and 40 response rates between secukinumab and adalimumab. 26 The national health insurance of South Korea is operated by the government and offers universal coverage. 27 Therefore, verification of macro-cost-effectiveness is very important to national budget management for health care.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no randomized controlled trials have directly compared secukinumab with other pharmacological agents in patients with AS. Matching-adjusted indirect comparisons have demonstrated no apparent differences in efficacy between secukinumab and adalimumab [ 45 ] or between secukinumab and golimumab [ 46 ] in placebo-anchored ASAS20/40 comparisons. In non-placebo-anchored analyses, secukinumab demonstrated higher ASAS20/40 response rates than adalimumab after week 12 [ 45 ] and golimumab at week 24 [ 46 ].…”
Section: Place Of Secukinumab In the Management Of Ankylosing Spondylmentioning
confidence: 99%
“…Matching-adjusted indirect comparisons have demonstrated no apparent differences in efficacy between secukinumab and adalimumab [ 45 ] or between secukinumab and golimumab [ 46 ] in placebo-anchored ASAS20/40 comparisons. In non-placebo-anchored analyses, secukinumab demonstrated higher ASAS20/40 response rates than adalimumab after week 12 [ 45 ] and golimumab at week 24 [ 46 ]. However, given the limitations of indirect comparisons, these results should be interpreted with caution.…”
Section: Place Of Secukinumab In the Management Of Ankylosing Spondylmentioning
confidence: 99%
“…As mentioned, there is currently only one direct head-to-head clinical study comparing outcomes in axSpA patients taking secukinumab versus those treated with the TNF inhibitor adalimumab, which is currently ongoing [ 22 ]. In the absence of direct comparisons, an indirect comparison of secukinumab and adalimumab was made using matching-adjusted data from the MEASURE 1 and 2 studies and from the ATLAS study with adalimumab [ 84 ]. There was no difference in ASAS20 or ASAS40 outcomes between secukinumab and adalimumab in the placebo-anchored comparison, but the unanchored comparisons significantly favored secukinumab for ASAS20 at weeks 16 and 24, and for ASAS40 at weeks 24 and 52 [ 84 ].…”
Section: Methodsmentioning
confidence: 99%